PENGARUH PENAMBAHAN POLISTIRENA TERHADAP SIFAT MEMBRAN SELULOSA ASETAT BERBAHAN DASAR LIMBAH TAHU - Jaka Rachmadetin (Widyariset, 2010)
Soybean curd whey, which is discarded as a waste, can be used as starting material for the preparation of cellulose and cellulose acetate membrane. However, due to its poor mechanical properties, blending with polystyrene will strengthen to the membrane. Nata de soya was made by soybean curd whey then was dried to produce cellulose flake. Cellulose flake was reacted with acetylation reagent, acetic anhydride, and other solvents to produce cellulose acetat flake. It was then mixed with polystyrene to form blend of cellulose acetate:polysyrene membrane with 100:0, 95:5, 90:10, 85:15, and 80:20 in ratios. These membranes were characterized by water flux, rejection index, and tensile strength. The results showed that cellulose acetate had produced a water content of 4.3%, and acetyl degree of 43.26% (equal to substitution degree of 2.8-3.0). The highest water flux membrane was made of 80:20 (164.23 l/m2., the highest rejection index was from 90:10 was 31.65%, and the highest tensile strength membrane was obtained from 80:20 (24.11 kgf). In conclusion the addition of polystyrene could increase the water flux and tensile strength of membrane, but it decrease the rejection index.